Share buybacks - Radzinski, Dirk (Centre for Law and Society, 2023)
Share buy-backs, the top candidates. That was the title of the front page of Finance Week, April 2, 1999. One cannot tell on first sight whether this is meant to be good or bad news, or relevant news at all. But the title indicates an increasing interest among financial analysts, whether firms will be able to buyback their own shares or not. After reading the article one can be certain. Share buybacks are supposed to be exactly what the capital markets always wanted to have, but what was always denied to them. The article demonstrates one vital reason why share buybacks are advantageous for companies: The signalling effect for the market. Although buybacks in certain situations are hardly helpful for the companies, they are generally treated as a panacea. That creates a loophole. Once a company announces its intention to repurchase its own shares, the share market price increases. Because of that knowledge management is enticed into manipulating the market price. The situation is fairly exaggerated, but elucidates a common problem on stock markets. The market price is not only a reflection of the company's performance, but is also influenced by psychological factors which appear to be almost irrational. Bearing that in mind, a discussion of a legal framework for the repurchase of shares is somewhat difficult, and weighing the advantages and disadvantages is, to a large extent, a matter of personal taste. south Africa was in good company in prohibiting repurchases of shares in general. Almost every state all over the world restricted share buybacks to the extent that they hardly ever took place. Off course there was one major exception: the United States of America. After following the early English case of Trevor v Whitworth in prohibiting share buybacks, state legislation and early decisions in the United States abolished the prohibition. Instead they chose directly the opposite. Only a few restrictions were imposed, and management was, and is, vastly free in buying and selling the shares of their company. The world noticed what happened in the United States, but especially lawyers and politicians of other countries always emphasised the risks of share repurchases. They stuck to their prohibitions, and did not think about reformations until very recently. Nowadays it seems that changing the regulations about share buybacks is en vogue. One could describe it as a race. Countries which have not changed their legislation yet are very concerned not to fall behind the standards set by other countries. 'Global market' is no longer just some jargon used in newspapers; it has become reality. Since the economics of countries all over the world are dependent upon major companies, which cater for employment and taxes, nobody wants to loose these companies as a result of domestic legislation restricting financial management. The constant pressure from managers and economists surely played a major role in starting the 'revolution'. Most of the European Union states have already changed their legislation as well as Australia and New. Zealand. South Africa is on the verge of doing so. The Bill has already been passed parliament and is signed by the president. The new provisions will come into force on June 1, 1999. That is reason and incentive to have a closer look at share buybacks, especially at the various legislation surrounding it. A comparative analysis is supported by the Constitution of South Africa. When interpreting the bill of rights a court, tribunal or forum may consider foreign law (section 39 (1)(c)). Generally the standpoint in South Africa is, one should always consider the legal developments in foreign countries. It facilitates the discussion about any change in laws. As a native German, the author wishes that a similar approach would be considered in Germany.